The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1615/jlongtermeffmedimplants.2021039830
|View full text |Cite
|
Sign up to set email alerts
|

Histological Evaluation of Bone Regeneration Using Hydroxyapatite Based Bone Substitute Derived from Antler: An Animal Study

Abstract: Objective: Guided bone regeneration (GBR) is considered as a prerequisite in some cases of implant dentistry. For this purpose, bone materials are commonly used. Calcium compounds and Ca-P based materials like hydroxyapatite (HA, Ca 10 (PO4) 6 (OH) 2 ), due to their similarity with the human bone, can be used as graft materials for bone regeneration. This study aimed to evaluate biocompatibility of antler xenograft and compare the osteoconduction effects of antler xenograft with Cerabone in regeneration of cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The excellent hydrophilicity of cerabone ® has been demonstrated via high-speed microscopical image analysis [16]. In accordance, an analysis of the regeneration capacity and immune response to xenogeneic and synthetic bone substitute materials showed that the xenogeneic cerabone ® induced a higher anti-inflammatory reaction [17][18][19]. Accordingly, a histologic, histomorphometric, and radiographic analysis of cerabone ® used in sinus floor elevation found that this bovine bone substitute material proved to be effective in slowly resorbing osseoconductive material [20].…”
Section: Bovine Bone Substitutesmentioning
confidence: 85%
See 1 more Smart Citation
“…The excellent hydrophilicity of cerabone ® has been demonstrated via high-speed microscopical image analysis [16]. In accordance, an analysis of the regeneration capacity and immune response to xenogeneic and synthetic bone substitute materials showed that the xenogeneic cerabone ® induced a higher anti-inflammatory reaction [17][18][19]. Accordingly, a histologic, histomorphometric, and radiographic analysis of cerabone ® used in sinus floor elevation found that this bovine bone substitute material proved to be effective in slowly resorbing osseoconductive material [20].…”
Section: Bovine Bone Substitutesmentioning
confidence: 85%
“…Like allogeneic grafts, they are processed and purified to minimize the risk of disease transmission and immunogenic reactions [7,54]. Xenogeneic bone substitutes also offer excellent osteoconductive properties, and have been widely used in dental implant procedures [7,[9][10][11][12][13]18,19]. In addition, high-temperature-treated bovine bone substitute materials such as cerabone ® provide long-term volume stability due to slow resorption [11].…”
Section: Alveolar Ridge Augmentationmentioning
confidence: 99%
“…It is processed at 1,200ºC and presents a less intense gradual release of calcium ions [16,22]. The use of this biomaterial has been reported by a few animal [23][24][25] and clinical studies [26,27]. Recently, it has been demonstrated that this xenograft supports the formation of new and stable bone volume in circumferential defects around implants in minipigs [28].…”
Section: Introductionmentioning
confidence: 99%